Frequency-Doubled Microwave Signal Generation and Phase Shifting With Arbitrary Signal Amplitude - Yang Chen (IEEE Photonics Journal, 2018)
A photonic-assisted frequency-doubled microwave signal generation and phase shifting approach with arbitrary signal amplitude is proposed. The key device in the proposed technique is a dual-polarization quadrature phase-shift keying modulator, whose two sub-dual-parallel Mach–Zehnder modulators are both biased as a carrier-suppressed single-sideband modulator but generating two opposite first-order optical sidebands. The phase difference between the orthogonally polarized two first-order optical sidebands and the polarization state of the optical signal are tuned independently by a polarization controller. After the optical signal from the polarization controller is combined via a polarizer and detected at a photodetector, a frequency-doubled microwave signal is generated, whose phase and amplitude can be independently controlled by tuning the polarization controller. An experiment is performed. Frequency-doubled microwave signals with carrier frequencies from 10 to 40 GHz are generated and phase shifted over 360° phase range with arbitrary signal amplitude. The proposed technique can not only be operated as a phase and amplitude tunable frequency-doubled microwave source, but also find applications in phased array radar systems as a wideband frequency-doubled multichannel phase shifter.